HAK ATAS KESEHATAN DAN TANGGUNG JAWAB NEGARA: KONSTRUKSI HUKUM DALAM PERLINDUNGAN PASIEN BPJS - Sartono, Sartono; Rahmat, Sandy Marzuqi; Arfiyah, Gemah; Prayuti, Yuyut (Jurnal Ilmiah Advokasi, 2025)
The right to health is a constitutionally recognized human right, and its fulfillment through the National Health Insurance (JKN) system is the responsibility of the state. This research aims to analyze and evaluate the effectiveness of legal regulations protecting BPJS patients in guaranteeing the right to health. The study employs a normative juridical approach to examine statutory regulations and an empirical juridical approach to observe their implementation in practice. Secondary data was collected from online media, complaint reports, and social media. The research findings indicate that while the regulations are comprehensive, their effectiveness is hindered by suboptimal implementation. This includes issues such as discrimination against BPJS Class 3 patients, limited facilities, and weak supervision and law enforcement. These disparities impede the achievement of substantive justice in healthcare services. Strengthening law enforcement, internalizing medical ethics, improving the supervisory system, and enhancing patient literacy and participation are therefore necessary.Keywords: Health rights, , National Health Insurance, Legal protection, Discrimination